51. Hand somatosensory Functional Source Separation (FSS) analysis reveals hypoactive sub-cortical source signals in migraine interictally. Issue 4 (April 2016) - Porcaro, C.; Lorenzo, G. Di; Seri, S.; Pierelli, F.; Tecchio, F.; Coppola, G.
Abstract : Recent morpho-functional evidences pointed out that abnormalities in the thalamus could play a major role in the expression of migraine neurophysiological and clinical correlates. To this aim, we used Functional Source Separation algorithm to extract, from EEG signals, the activity of different neuronal pools recruited at different latencies along the somatosensory pathway in interictal migraine without aura (MO) patients. Twenty MO patients and twenty healthy volunteers (HV) underwent EEG recording. Four functional sources, two sub-cortical (FS14 at brainstem and FS16 at thalamic level) and two cortical (FS20 radial and FS22 tangential parietal), were extracted along the somatosensory pathway in response to the median nerve stimulation. High-frequency oscillatory (HFO) was extracted using band-pass digital filter (450–750 Hz) from the broadband EEG signal. Significant HFO reduction in the sub-cortical FS14 and FS16 were observed for the MO patients compared to the HV. No significant differences were reached, instead, for the cortical ones. Reduced sub-cortical brainstem and thalamic HFO activations play an important role in MO patients. Present results are the first neurophysiological evidence supporting the hypothesis that a functional disconnection of the thalamus from the subcortical monoaminergic system may underline the interictal cortical abnormal information processing in migraine.